Sexuality in a changing China : young women, sex and intimate relations in the reform period - Zarafonetis, Nicole (Routledge, 2017)
China has experienced rapid economic and social change since the beginning of the 'Open Door' policy in 1978. Yet at the same time, the legacy of the Mao era remains and elements of Confucianism continue to exist in the reform period. As a result, traditional views concerning gender roles and sexual attitudes and practices persist. Based on interviews with forty-three women in Shanghai, this book investigates the way in which young women, born under the one child policy in China, consider sexuality and intimate relations in the 21st Century. Covering their thoughts and views on issues such as sex education, the rise of 'dating culture' and 'ideal' husbands, it is argued that reform China offers young women a series of contradictory expectations of sex and relationships. Despite the Party-State rhetoric of equality, participant narratives ultimately highlight the limited discourse of desire and sexual autonomy available to young women, the prevalence of essentialist notions of femininity and masculinity and the continuing norm of marriage as the only legitimate context for female sexual expression. 0.
Keywords: Sex -- China.; Sex instruction -- China.; Sex role -- China.; Dating (Social customs) -- China.; Marriage -- China.; Women -- China -- Social conditions.; Sexualité -- Chine.; Éducation sexuelle -- Chine.; Rôle selon le sexe -- Chine.; Amours -- Chine.; Mariage -- Chine.; Femmes -- Chine -- Conditions sociales.; POLITICAL SCIENCE -- Public Policy -- Cultural Policy.; SOCIAL SCIENCE -- Anthropology -- Cultural.; SOCIAL SCIENCE -- Popular Culture.; Dating (Social customs); Marriage; Sex; Sex instruction; Sex role; Women -- Social conditions; China; Junge Frau; Geschlechterrolle; Sexualverhalten; Partnerwahl; Soziale Norm